(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Microfinance Human Resource I project is a web-based system that offers several HR services, including competency management, recruitment and applicant management, learning and training management, newly hired onboarding, employee self-service, performance management, social recognition, and succession planning. Some organizations utilize human resources for effective decision-making processes. However, they struggle with productivity due to various issues, including manual data collection, lack of email verification, and improper storage of confidential information. To resolve the problem, the project team developed a web-based system to support and manage the organization by reducing time-fill productivity, securing data, and boosting workforce engagement to improve productivity and make a significant employee commitment. The project team employed agile methodologies to ensure the prompt completion of HR management tasks and prioritized the production of high-quality deliverables. Consequently, The Project team created a web-based system that efficiently streamlines and manages various HR operations, such as email communication, secure data management, and a manageable shortlisting process. These accomplishments have led to notable improvements within the organization. The web-based platform Microfinance Management System Human Resource 1 focuses on improving various processes to create better transactions, enhance data security, and fill the gap so that each process inside the organization is more convenient and organized.